The Terminological Polyhedron in LGBTQ Terminology: Self-Naming as a Power to Empower in Knowledge Organization - Campbell, D. Grant [UNESP]; Chaves Guimaraes, Jose Augusto; Pinho, Fabio Assis; Martinez-Avila, Daniel; Nascimento, Francisco Arrais (Ergon-verlag, 2017)
This paper uses Hope Olson's concept of the power to name to explore the terminological practices of the LGBTQ community in the Cariri region of Brazil in the years between 2006 and 2013. LGBTQ communities can seize back the power to name, traditionally exerted by a heteronormative society upon marginalized groups, by organizing their cultural and practical knowledge from within and by exercising the power to name themselves and their specific domains and cultural practices. The study showed that knowledge organization-the act of defining entities and categories and assigning specific names to them-is a gesture of self-empowerment on many different levels. The power of self-naming in this LGBTQ community is a polyhedron in which some facets are frequent, such as the power to empower or affirm an identity. On the one hand, the names and categories break through gender, geographical and temporal specificity to embrace terms, names, and idioms drawn from a range of different countries, traditions, languages, and time periods. On the other hand, these names and categories work to reinforce and affirm the geographical and cultural specificity of the Cariri region itself, embedding its pride and self-affirmation within the varied languages and heteronormative history of Portuguese colonization in that region. In selecting terms and categories to name, organize, and celebrate their identities, the LGBTQ people of Cariri have taken the power to name: not as information intermediaries striving for objectivity and neutrality but as committed members of a marginalized but vital community.
Keywords: terms; knowledge organization; power; lgbtq